Impact of Behavioural Integration of Senior Management in Effectiveness of Strategic Decision-Making: An Applied Study in Some Iraqi Private Faculties in Kerbala City - Fadhil, Alaa Hussein; Amanah, Ahmed Abdullah; Hussein, Sahar Abbas; Hasan, Mohammed Faez; Mohammed Ali, Ghaith Saadi; Mohammed, Ihab Zeyad (Technium Social Sciences Journal, 2023)
This study sheds light on role of behavioral integration of senior management in effectiveness of strategic decision-making processes at the level of Iraqi private educational institutions. The goal of research was to focus attention of administration of private colleges, research community, to importance of the integrative behavioral role of senior administration in effectiveness of process of making its strategic decisions. Private colleges scattered in Karbala governorate were chosen as a community for research, as questionnaire was distributed to an intentional sample of (61) respondents from members of councils, directors of branches and departments, and officials of people and units in private colleges. Some statistical indicators (descriptive and analytical) were used using statistical program (SPSS V.28). Most important finding of research is existence of a correlation relationship and a moral effect between research variables included in first and second main hypothesis in order to achieve effectiveness of strategic decision-making by adopting integrative behavioral role of senior management members in the private colleges operating in holy governorate of Karbala.